CT-based airway flow model to assess ventilation in chronic obstructive pulmonary disease: a pilot study - Kim, M; Doganay, O; Matin, TN; Povey, T; Gleeson, FV (Radiological Society of North America, 2019)
Background The lack of functional information in thoracic CT remains a limitation of its use in the clinical management of chronic obstructive pulmonary disease (COPD).